International encyclopedia of organization studies - Clegg, Stewart; Bailey, James Russell 1963-; Gale Group (Los Angeles, Calif. Sage Publications, 2008)
Offers a comprehensive overview of many of the major ideas, concepts, terms, and approaches that characterize this diverse field of organization studies. Illustrates the fluidity, dynamism, and innovation that now occur in organization studies-internationally. Examines how organizations are devices for structuring life and lives are structured by organizations.
Editorial board -- List of entries -- Reader's guide -- About the general editors -- About the associate editors -- List of contributors -- Introduction -- Entries -- Volume 1: A-D -- Volume 2: E-L -- Volume 3: M-O -- Volume 4: P-Z -- Index.
Electronic reproduction.
Keywords: Organization -- Encyclopedias; Organizational sociology -- Encyclopedias; Organizational behavior -- Encyclopedias; Management -- Encyclopedias; Electronic books